Sosialisasi Teknik Pembuatan Video Kreatif dan Strategi Pemasaran Digital sebagai Langkah Inovatif bagi Mahasiswa Universitas Trunojoyo Madura - Putri, Devi Amelia; Isnaini, Nur; Rifqi, Moch. Zainul (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
In the era of digital information, business, expecially MSME, are embracing digital marketing as a strategic tool to capture consumer attention. attention. This approach offers numerous advantages, including increased reach, speed, precision, and cost-effectiveness. Delivery on digital media, such as social media, is also a form of promotion, product introduction, and communication between buyers and consumers. The socialization service activities for students at Trunojoyo University Madura aims to provide insight, understanding of how to market products through creative and interesting video content so that consumers are interested in buying. The target of the socialization activities carried out by group 5 is Trunojoyo Madura University students. The method of implementing the service activities of group 5 Denaya Project MBKM Entrepreneurship was the program socialization by providing direct understanding to several students who attended the activity. The implementation of the activity was divided into several activities, including: (1) the planning stage, (2) implementation, and (3) evaluation. From the activities that have been carried out, it can be concluded that the approach and direct communication to the students as the audience are enthusiastic in participating in this socialization until completion. This service activity is able to increase students' understanding of digital marketing and creative video making techniques, which aims to increase audience motivation to participate in the socialization event